KONOTATIF CIGULU-CIGULU DALAM BAHASA MELAYU MANADO (BMM) - Rawung, Willem Hanny; Kalangi, Leika M V.; Pamantung, Rina (Kajian Linguistik, 2019)
AbstractCigulu-cigulu is a form of a riddle game. A question or a statement was delivered and then the other person or the interlocuters must find the appropiate answer or the respond for the said question or statement. Cigulu-cigulu is the abbreviated form of "cigi kong gulung-gulung in Manado Malay (BMM), If translated to Bahasa Indonesia it means "tarik lalu digulung" (pull then roll). The research method used to find connotative meanings in cigulu-cigulu is a qualitative descriptive method with the intention of understanding phenomena experienced by informants such as behavior, perception, motivation, etc. by means of descriptions in the form of words and language in a specific context that is natural and by utilizing natural methods. The results showed that in cigulu-cigulu found connotative meaning both positive and negative. Positive when statements / questions are submitted or answers to statements / statements; vice versa. Generally cigulu-cigulu associated with food. The food in question is typical or traditional food from Manado. Semantically this is motivated because Manado have varieties of delicious food. Manadonese people are also known to likely state everything directly, not ashamed to express something "taboo" which for some other communities / cultures are considered uncultured or even forbidden to say.Keywords: cigulu-cigulu, BMM, connotative meaning